The space in-between in the Latin American literature: the case of Cesar Moro and Jose Maria Arguedas - Fernández Cozman, Camilo Rubén (2017)
There is no cultural identity, there are always cultural identities that belonged to decentered subjects talking from different discursive positions. The space in-between is a category supported by Silviano Santiago to consider that a subject does not speak from a specific locus, but from different places. Cesar Moro Hispanized French as to Jose Maria Arguedas Quechuasized Spanish. However, both are a critique of the Spanish invasion, questioning what is happening from different perspectives. In order to do this, "Biografía peruana (muralla de seda)" ("Peruvian biography - the wall of silk") by Moro and some passages of "Los ríos profundos" ('Deep rivers') by Arguedas will be analyzed in order to consider the role assumed by the Latin American writer in a postcolonial society such as she Peruvian.